2014
DOI: 10.1002/jbm.a.35291
|View full text |Cite
|
Sign up to set email alerts
|

Whole-organ tissue engineering: Decellularization and recellularization of three-dimensional matrix liver scaffolds

Abstract: To report the results of whole liver decellularization by two different methods. To present the results of grafting rat and sheep decellularized liver matrix (DLM) into the normal rat liver and compare natural cell seeding process in homo/xenograft of DLM. To compare the results of in vitro whole liver recellularization with rats' neonatal green fluorescent protein (GFP)-positive hepatic cells with outcomes of in vivo recellularization process. Whole liver of 8 rats and 4 sheep were resected and cannulated via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 29 publications
0
86
0
2
Order By: Relevance
“…6B, day 7) in agreement with other reports using different sources of hepatocytes. 5,12 An increasing trend in overall HepG2 metabolic activity was observed, and resazurin reduction (and calculated cell number) was significantly higher after 5 ( p = 0.002) and 7 days ( p < 0.001) of perfusion culture compared to 3 days (Fig. 6C).…”
Section: Figmentioning
confidence: 90%
See 1 more Smart Citation
“…6B, day 7) in agreement with other reports using different sources of hepatocytes. 5,12 An increasing trend in overall HepG2 metabolic activity was observed, and resazurin reduction (and calculated cell number) was significantly higher after 5 ( p = 0.002) and 7 days ( p < 0.001) of perfusion culture compared to 3 days (Fig. 6C).…”
Section: Figmentioning
confidence: 90%
“…Decellularization of livers and kidneys through perfusion of detergent solutions through the vasculature has been well documented 3,4 -with technical feasibility demonstrated using both large animal and humanscale organs [5][6][7][8] as well as small animal organs for repopulation with stem or immature progenitor cells. 7,[9][10][11][12][13] The current challenges and limitations to organ and tissue engineering have shifted to the cellular repopulation phase of tissue development where donor cells are reintroduced into wholeorgan ECM scaffolds; however, very little detail is typically provided describing bioreactor construction despite the identification of specific design features that are critical to optimize scaffold recellularization and overall function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that decellularized matrix based tissue regeneration is feasible for many hollow and parenchyma organs, such as bladder, 8 skin, 9 blood vessels, 10 heart, 11 lung, 12 kidney, 13 as well as liver. 14 Nonetheless, potential clinical application of DLM-based HLT may be plagued by the selection of scaffold source, considering that human derived DLM is also insufficient, and the application of xenogeneic DLM is hindered by potential risks of zoonosis and immunological rejection. Herein, in order to expand the scaffold donor pool, we have established the decellularized spleen matrix (DSM), which had homogeneous ECM with DLM, and presented comparable condition for hepatocyte cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…В литературе описаны успешные эксперимен-ты по децеллюляризации целой печени животных: крыс [4], кроликов [5], свиньи [6]. Также описан эксперимент по децеллюляризации левой латераль-ной доли, взятой у пациента с гемангиомой пече-ни [7].…”
Section: Abstract: Liver Decellularization Extracellular Matrix Tunclassified